Faktor-Faktor yang Mempengaruhi Produksi Padi di Kecamatan Kuranji Kota Padang Provinsi Sumatera Barat - Leovita, Angelia; Martadona, Ilham (Department of Agribusiness, Halu Oleo University, 2021)
Rice is the most widely cultivated commodity by farmers in Indonesia. In addition, it is also the primary commodity of food crops that become the leading food ingredient of Indonesian people. Along with the increasing population of Indonesia, the need for rice will also increase. This research aims to determine the factors that affect rice production in the Kuranji District of Padang City of West Sumatra Province. This research was conducted from February - May. Kuranji subdistrict election was conducted purposively, considering that the subdistrict is one of the rice production centers in Padang City. The data used in this study is primary data. The study used quantitative data analysis — a sampling technique with snowball sampling techniques with 30 respondents. The method used in this study in analyzing the factors that affect rice production is the regression analysis of the Cobb-Douglas production function model. The results showed that land area variables, seed variables, fertilizer variables, labor variables outside the family, and labor variables in families were influential and had positive coefficients. In contrast, variables that have no natural effect on rice production at the level of 5 percent are variables in land and seed area.